2018
DOI: 10.1186/s12938-018-0478-4
|View full text |Cite
|
Sign up to set email alerts
|

In vivo degradation and neovascularization of silk fibroin implants monitored by multiple modes ultrasound for surgical applications

Abstract: BackgroundIn this paper we aimed to investigate the neovascularization and biodegradation of the silk fibroin in vivo using multiple modes ultrasound, including two-dimensional, three-dimensional and contrast-enhanced ultrasound by quantifying the echo intensity, volume and contrast enhancement of the silk fibroin implants.MethodA total of 56 male Wistar rats were randomly divided into two groups and 4%(w/v) silk hydrogels were injected subcutaneously at hind limb or upper back of the rats respectively to comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 34 publications
(31 reference statements)
0
21
2
Order By: Relevance
“…In the later stage, the echo of the sample was lower than that of the muscle. The echo of the SF scaffold during ultrasound in this study was different from the ndings by Li et al [22]. This is possible because SF can be processed into different constructs (e.g., porous scaffolds, lms, hydrogels, and nano/microspheres).…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…In the later stage, the echo of the sample was lower than that of the muscle. The echo of the SF scaffold during ultrasound in this study was different from the ndings by Li et al [22]. This is possible because SF can be processed into different constructs (e.g., porous scaffolds, lms, hydrogels, and nano/microspheres).…”
Section: Discussioncontrasting
confidence: 80%
“…It has been used in research that involves degrading biological materials; however, it is rarely used when researching SF scaffolds. Li et al [22] investigated the neovascularization and biodegradation of an SF gel in vivo using multiple mode ultrasound by quantifying the echo intensity, volume, and contrast enhancement of the SF gel implants. It showed that the silk gel implants appear as hypoechoic nodules in the early stages of the degradation, and there are clear boundaries under the skin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Silk fiber processing solvents can affect the secondary structure and biodegradability of silk. Organic solvent-based silk takes a year or more to get completely absorbed in vivo (Zhang et al, 2009 ), while aqueous solvent-based silk only requires a maximum of 6 months to get completely absorbed in vivo (Li S. et al, 2018 ). This property is helpful in repairing critical bone defects as silk scaffolds can provide sufficient structural support until native bone is completely regenerated (Mandal and Kundu, 2009 ).…”
Section: Natural Polymers: Organic Biomaterials Extracted From Organismentioning
confidence: 99%
“…The development of silk fibroin properties is very important in order to meet various application requirements. Therefore, researchers have carried out a variety of studies aimed at extending the application of silk fibroin from hydrophobic to hydrophilic material [47,48], as well as from filaments to films, sheets, and scaffolds [46,49,50].…”
Section: Introductionmentioning
confidence: 99%